2018
DOI: 10.1371/journal.pone.0191630
|View full text |Cite
|
Sign up to set email alerts
|

Body fat distribution and risk of incident ischemic stroke in men and women aged 50 to 74 years from the general population. The KORA Augsburg cohort study

Abstract: BackgroundIt remains controversial whether measures of general or abdominal adiposity are better risk predictors for ischemic stroke. Furthermore, so far it is unclear whether body fat mass index (BFMI) and fat free mass index (FFMI) are risk predictors for ischemic stroke. This study examined the sex-specific relevance of body mass index (BMI), BROCA Index, waist circumference (WC), waist-height ratio (WHtR), BFMI and FFMI for the development of ischemic stroke in a Caucasian population.Material and methodsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 41 publications
0
16
0
1
Order By: Relevance
“…Comparing the four anthropometric indexes and identifying the index that was most closely related to stroke were very important for the primary prevention of stroke in Jilin province. A similar study explored the association between body fat distribution and the risk of incident ischemic stroke (28). Their results showed that waist circumference or waist-to-height ratio was superior to BMI in predicting the risk of ischemic stroke.…”
Section: Figure 1 | Association Between Stroke and Bmi Quartiles (A)mentioning
confidence: 99%
“…Comparing the four anthropometric indexes and identifying the index that was most closely related to stroke were very important for the primary prevention of stroke in Jilin province. A similar study explored the association between body fat distribution and the risk of incident ischemic stroke (28). Their results showed that waist circumference or waist-to-height ratio was superior to BMI in predicting the risk of ischemic stroke.…”
Section: Figure 1 | Association Between Stroke and Bmi Quartiles (A)mentioning
confidence: 99%
“…In addition, by using diet- or genetic-induced obesity, the body and vasculature of the animal is still young, rather than middle aged. These points are critically significant because obesity may be more common in aging women and may confer greater risk for secondary health issues such as ischemic stroke ( 1 , 4 , 5 , 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the menopausal transition is associated with a significant increase in body weight and abdominal fat in middle-aged females ( 7 ). In addition, studies suggest that abdominal obesity may contribute to a greater risk for ischemic stroke in women than in men ( 1 , 8 , 9 ). The reasons for the sex differences in obesity and risk of stroke in middle-aged men and women are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, BMI as a stroke risk predictor has its limitations. A prospective population-based study published in 2018 by Zahn et al [7] showed that BMI is not associated with the incidence of ischemic stroke. A similar result was obtained by Seung-Han Suk et al [8], in which BMI was not significantly associated with ischemic stroke incidence.…”
Section: Introductionmentioning
confidence: 99%